1987
DOI: 10.2190/gcaa-lc01-q8d0-r2f6
|View full text |Cite
|
Sign up to set email alerts
|

Age and Present and Future Perceived Quality of Life

Abstract: Future expectations of quality of life and present evaluations of quality of life were measured in three age groups using four measures. Expectations were found to exceed present evaluations on all four measures. There was a significant correlation between age and the Faces Scale for future expectations. Age also related to differences between future expectations and present quality of life estimates. Expectations, the cognitive dimension of hope, merit more intensive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Studies that show adults perceive increased risk of decline and decreased potential for personal growth across the life cycle (Heckhausen et al, 1989) as well as age-related declines in goal seeking and positive expectations concerning oneself and one's future life (Reker, Peacock, & Wong, 1987) also converge with these findings. There are, however, exceptions: Staats and Stassen (1987) showed expectations for future quality of life that exceeded present evaluations, although their oldest respondents were considerably younger than those included in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…Studies that show adults perceive increased risk of decline and decreased potential for personal growth across the life cycle (Heckhausen et al, 1989) as well as age-related declines in goal seeking and positive expectations concerning oneself and one's future life (Reker, Peacock, & Wong, 1987) also converge with these findings. There are, however, exceptions: Staats and Stassen (1987) showed expectations for future quality of life that exceeded present evaluations, although their oldest respondents were considerably younger than those included in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…Because the proportion of older persons is increasing, their perceptions of future as well as present well-being are important. Hope, future time perspective, and cognitions about the future may change across the life span and may also be different for various cohorts of individuals (Ryff, 1989; Staats & Stassen, 1987). However, the notion that plans, hopes for the future self, and a future time perspective are maintained in most older adults is supported by the research of Hooker (1992) on possible selves in older adults and Holahan's (1988) research on life goals at 70 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of cancer itself at a younger age may impact on subsequent health behaviour in older age (Benyamini et al 2003). Other studies have shown that increasing age is associated with decreasing health and QOL (Farquhar 1995) and differing expectations of QOL (Staats & Stassen 1987). Measures such as the EUROQOL or SF-36 have demonstrated a heavy response burden and increased requirement for interview administration with advancing age (Brazier et al 1996).…”
Section: The Consequences Of Applying Cur Rent Approaches To Health Omentioning
confidence: 99%